Absenteeism and job satisfaction in a portuguese municipality - Ribeiro, Maria Isabel (2019)
Absenteeism has a direct impact on the quality of the service provided by the municipality to its citizens. Therefore, the objective of this research is to analyse the correlation between work absenteeism at the Bragança municipality, Portugal and job satisfaction; to identify factors concerning the type of work as well as the worker’s attitudes, behaviours and values which may be correlated to job satisfaction. To achieve these objectives, it was developed a quantitative and cross-sectional study based on a survey directly administered to the municipality workers. Spearman’s test was used to study the correlation at a 5% level of significance. From the 71 workers surveyed, 28 had already been absent from the workplace. Workers justified their absence with short-term sickness (14.1), family caregiving (12.7%) and long-term sickness (7.0%). The correlation between absenteeism and job satisfaction was not verified. However, correlations were observed between job satisfaction and type of work (Sig.< 0.05). Although no statistically significant correlation was found between job satisfaction and absenteeism, there are some factors associated with the type of work and with workers’ attitudes, behaviours and goals which showed to be correlated to job satisfaction. Therefore, it is recommendable that executive managers continue to improve work conditions in order to increase the productivity, quality and efficiency of the service provided to citizens.